2018
DOI: 10.1111/tbed.12826
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of brucellosis in goats and sheep in Thailand: Results from the Thai National Brucellosis Surveillance System from 2013 to 2015

Abstract: In Thailand, brucellosis re-emerged in humans in 2003 and is considered a public health risk to goat farmers as the disease is endemic in small ruminants. The Thai Department of Livestock Development (DLD) established a nationwide surveillance system for brucellosis in goats and sheep in 1997. Using data from this surveillance system, we describe the seroprevalence of brucellosis from 2013 to 2015 in small ruminants and the spatial distribution of the disease throughout Thailand. Surveillance data collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In contrast to our findings, some previous studies showed lower prevalence rates of small ruminant brucellosis such as 1.79% in Tselemti district, Northern Ethiopia [ 45 ], 1.8% in Debre Zeit and Modjo export abattoirs of Oromia Regional State of Ethiopia [ 46 ], 1.2% in Gambia [ 47 ], 5.1% in different farms of Punjab, Pakistan [ 36 ], 6.26% in Southeast Europe [ 48 ], 0.4% in Northwest Ethiopia [ 49 ], 3.4% in Quetta and its surrounding areas of Pakistan [ 50 ], 3.2% in Borena, Southern Ethiopia [ 51 ], and 4.5% in China [ 52 ]. On the other hand, as compared to our findings, higher prevalence rates had also been reported in some parts of the world including South Omo Zone, Ethiopia [ 53 ], Iraq [ 54 ], India [ 23 ], Thailand [ 55 ], Nigeria [ 56 ], and Jordan [ 57 ]. The varied prevalence rates of brucellosis in different regions might be due to differences in sensitivities and specificities of techniques used for diagnosis of bacteria, husbandry practices, and geoclimatic conditions which might be more suitable (for bacteria to grow) in regions with higher prevalence rates [ 58 ].…”
Section: Discussionsupporting
confidence: 71%
“…In contrast to our findings, some previous studies showed lower prevalence rates of small ruminant brucellosis such as 1.79% in Tselemti district, Northern Ethiopia [ 45 ], 1.8% in Debre Zeit and Modjo export abattoirs of Oromia Regional State of Ethiopia [ 46 ], 1.2% in Gambia [ 47 ], 5.1% in different farms of Punjab, Pakistan [ 36 ], 6.26% in Southeast Europe [ 48 ], 0.4% in Northwest Ethiopia [ 49 ], 3.4% in Quetta and its surrounding areas of Pakistan [ 50 ], 3.2% in Borena, Southern Ethiopia [ 51 ], and 4.5% in China [ 52 ]. On the other hand, as compared to our findings, higher prevalence rates had also been reported in some parts of the world including South Omo Zone, Ethiopia [ 53 ], Iraq [ 54 ], India [ 23 ], Thailand [ 55 ], Nigeria [ 56 ], and Jordan [ 57 ]. The varied prevalence rates of brucellosis in different regions might be due to differences in sensitivities and specificities of techniques used for diagnosis of bacteria, husbandry practices, and geoclimatic conditions which might be more suitable (for bacteria to grow) in regions with higher prevalence rates [ 58 ].…”
Section: Discussionsupporting
confidence: 71%
“…Research and development for other endemic diseases like FMD, HS, and brucellosis is still ongoing (75)(76)(77). Culling livestock infected with zoonotic diseases (e.g., bTB, brucellosis) is commonly implemented in Thailand (78,79). However, infected animals often undergo illegal translocation, potentially spreading the disease to other locations.…”
Section: Discussionmentioning
confidence: 99%
“…reported in Chiang Rai, Thailand was 3.3% in dairy cattle [ 39 ]. Other studies in Thailand reported that seroprevalences were 1.4% in goats and 1.6% in sheep in 2013 [ 40 ] and overall 0.72% in small ruminants between 2013 and 2015 [ 41 ]. It is interesting that brucellosis is not a prevalent infection in cattle in this tropical, low-density production system.…”
Section: Discussionmentioning
confidence: 99%